PERILAKU KONSUMTIF PEMBELIAN PRODUK KOSMETIK PADA REMAJA PUTRI DI SMP NASIMA SEMARANG DITINJAU DARI GAYA HIDUP HEDONIS - Naomi Mutiara Erika; Brigitan Argasiam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2023)
This research aims to determine whether there is a relationship between hedonistic lifestyle and consumptive behavior in purchasing cosmetic products among teenage girls at SMP Nasima Semarang with a sample size of 136 students. Data collection was done using a consumptive behavior scale consisting of 24 items using a sampling technique. Data analysis was conducted using the Rank Spearman correlation statistical technique, with the assistance of SPSS 26. The research data analysis results obtained a correlation value of 0.136 between the hedonistic lifestyle and consumptive behavior in purchasing cosmetics at SMP Nasima Semarang, with the highest significant value of 0.000, thus accepting the hypothesis. The effective contribution of the hedonistic lifestyle to consumptive behavior is 72.1%, while the remaining 27.9% is influenced by other factors. Keywords : Hedonistic lifestyle, Consumptive behavior